2017
DOI: 10.1038/s41522-017-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

Hidden biofilms in a far northern lake and implications for the changing Arctic

Abstract: Shallow lakes are common across the Arctic landscape and their ecosystem productivity is often dominated by benthic, cyanobacterial biofilms. Many of these water bodies freeze to the bottom and are biologically inactive during winter, but full freeze-up is becoming less common with Arctic warming. Here we analyzed the microbiome structure of newly discovered biofilms at the deepest site of a perennially ice-covered High Arctic lake as a model of polar microbial communities that remain unfrozen throughout the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 21 publications
4
39
0
Order By: Relevance
“…We conclude that the microbiota of both polar regions may be more connected than previously assumed and our data suggest a biogeographical connection between both poles, consistent with some previous studies Jungblut et al, 2010;Chrismas et al, 2015;Cox et al, 2016;Biersma et al, 2017;Mohit et al, 2017). The polar microbial communities in our study are an assemblage of ubiquitously-distributed and potentially endemic taxa.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We conclude that the microbiota of both polar regions may be more connected than previously assumed and our data suggest a biogeographical connection between both poles, consistent with some previous studies Jungblut et al, 2010;Chrismas et al, 2015;Cox et al, 2016;Biersma et al, 2017;Mohit et al, 2017). The polar microbial communities in our study are an assemblage of ubiquitously-distributed and potentially endemic taxa.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest that the global dispersal of certain (microbial) species is combined with environmental selection shaping bacterial communities in the polar regions (Vyverman et al, 2010;Chong et al, 2015;Cox et al, 2016), though temporal (Rochera et al, 2010) or spatial (Villaescusa et al, 2013) variability in environmental conditions can cause differences among prokaryotic meta-communities in polar habitats. Highly seasonal conditions in the polar regions (Chong et al, 2015), such as the absence of light in winter (Alonso-Saez et al, 2012) freezing and limited freshwater availability Mohit et al, 2017) and low temperatures (Yergeau et al, 2007(Yergeau et al, , 2012Kleinteich et al, 2012) may cause the observed differences between polar and non-polar communities, since non-polar regions exhibit more moderate environmental conditions. In fact, large differences in temperature and annual solar radiation but not regional precipitation explained community differences in the present dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, culture-independent studies of microbial communities in Arctic lakes have been most 50 often performed by amplifying and sequencing taxonomic markers like the 16S rRNA gene (e.g., 51 Crump et al, 2012;Mohit et al, 2017;Ruuskanen et al, 2018;Stoeva et al, 2014;Wang et al, 2016Wang et al, , 52 2019). However, amplicon-based methods are subject to PCR amplification bias, which might alter the 53 estimates of microbial community composition and diversity.…”
Section: Introduction 36mentioning
confidence: 99%
“…Cyanobacterial mats are found in both the depths of lakes and their shallow moats (Jungblut et al, ; Mohit, Culley, Lovejoy, Bouchard, & Vincent, ; Zhang et al, ). Deep mats are distinctly laminated, sometimes forming large pinnacles, while those at lake margins and in shallow pools are less structurally complex.…”
Section: Introductionmentioning
confidence: 99%